DETERMINATION OF Chlorella sp. YIELDEXTRACTED WITH DIFFERENT SOLVENT - fajrifa, Eldya novri; Iriani, Dian; Sari, N. Ira (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2022)
Abstract Chlorella sp. is green microalgae thatcontain bioactive compounds which can be used as biological functions.This chlorella was obtained from a sea of Bagansiapiapi waters. The purpose of this study was to obtain the best yield value of Chlorella sp.extractedwith a different solvent. The experimental research method consisted of 3 stages, namely: 1) sample preparation, 2) sample extraction with different solvents, 3) yield testing. The design used was a non-factorial Completely Randomized Design (CRD) with 4 treatment levels using different solvents: n-hexane (N1), ethyl acetate (N2), methanol (N3) and aquades (N4) with 3 replications, so obtained 12 experimental units. The results showed that the Chlorella sp. was extracted withn-hexane solvent (N1) was the best treatment containing the highest yield ofChlorella sp.(51.17%), followed by methanol solvent (50.76%), aquades (34.71%) and ethyl acetate (26.09%). Therefore, n-hexane is more effectively usedto extract Chlorella sp.Key words: Chlorella sp, Different solvents, Yield